Changes in Manual Dexterity in Ontogenesis - Nowicki, Grzegorz (Anthropological Review, 1988)
8,509 males and 9,680 females were examined to discover the changes in manual dexterity during ontogenesis. The research was carried out in the Bydgoskie, Toruńskie, and , Włocławskie1 voivodships.